Does it (Re)pay to be Female? Considering Gender in Microfinance Loan Officer-Client Pairs. Issue 2 (1st February 2022) - Otiti, Naome; Godfroid, Cécile; Mersland, Roy; D'Espallier, Bert
Abstract: This paper examines the effect of the gender combination of client-loan officer pairs on loan repayment in an Ecuadorian microfinance institution. We show that among the four possible client-loan officer gender pairs i.e. female client-female loan officer, female client-male loan officer, male client-male loan officer and male client-female loan officer, the most favourable pairs in terms of repayment are those with female loan officers whereas the least favourable are those with male loan officers. We also show that repayment is even further enhanced for all client-loan officer pairs when the client's previous loan officer was a woman. Our findings point to relational differences between male and female loan officers when interacting with microfinance clients, which is also highlighted by our qualitative insights from the field.